A Review on the Addictive Materials Paan Masala (Paan Parag) and Nass (Naswar) - Tayebeh Nakhaei Moghaddam; Faramarz Mobaraki; Mohammad Reza Darvish Moghaddam; Maryam Jafardokht Bonjar (Ital Publication, 2019)
There are many reasons why people use addictive substances including the euphoric and stimulating effects they have. This article introduces the addictive substances Paan, Naswar, nicotine, and other related products. It also deals with their use by people who are not aware of their addictive properties and use them for their side effects as mouth freshener and tasty and fragrant snacks. Furthermore, they are marketed in beautiful and attractive packages for various age groups, even children and adolescents (who inadvertently use them, without being aware of their effects and over time become addicted to them). Therefore, providing information to, and constant education of, target groups can be effective in improving the public health.